The Relation between the Blood Groups, Rhesus Factor, and Breast Cancer in the Holy Karbala Governorate - Ahmed Khudhair Abdulridha AL-Ganimi (University of Thi-Qar Journal of Science, 2020)
The distribution ABO blood groups among patients with breast cancer were as follow: blood group type O (40.8%), blood group type A (25.0%), B (23.7%), and AB (10.4%), for the donor’s healthy control, ABO blood groups percentages were as follow: type O (39.9%) type A (28.1%), type B (22.0%), and type AB (9.9%). There is no significant association between blood types ABO and the breast cancer. (P > 0.05) Rh factor has a significant difference between patients with breast cancer and healthy control (P=0.002). There were significant differences in age categories among patients with breast cancer and controls. (p= 0.000) .